2008
DOI: 10.1158/0008-5472.can-08-1973
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Glypican 3 Antibody as a Potential Antitumor Agent for Human Liver Cancer

Abstract: Human glypican 3 (GPC3) is preferentially expressed in the tumor tissues of liver cancer patients. In this study, we obtained a monoclonal antibody (mAb) against the COOHterminal part of GPC3, which induced antibody-dependent cellular cytotoxicity (ADCC). The mAb, designated GC33, exhibited marked tumor growth inhibition of s.c. transplanted Hep G2 and HuH-7 xenografts that expressed GPC3 but did not inhibit growth of the SK-HEP-1 that was negative for GPC3. GC33 was efficacious even in an orthotopic model; it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 30 publications
7
127
0
Order By: Relevance
“…Comparative studies with the parental GC33 antibody show similar results in the xenograft model. Ishiguro et al, show that, in addition to inhibiting tumor growth in an orthotopic Hep G2 xenograft model, they could dramatically reduce the expression of AFP after treatment with GC33 at a dose of 5 mg/kg [39]. Animals were inoculated with 5 × 10 6 Hep G2 cells and after 21 days were administered anti-GC33 antibody or vehicle.…”
Section: Glypican 3 Targeted Therapy; Antibody-based Approachmentioning
confidence: 99%
“…Comparative studies with the parental GC33 antibody show similar results in the xenograft model. Ishiguro et al, show that, in addition to inhibiting tumor growth in an orthotopic Hep G2 xenograft model, they could dramatically reduce the expression of AFP after treatment with GC33 at a dose of 5 mg/kg [39]. Animals were inoculated with 5 × 10 6 Hep G2 cells and after 21 days were administered anti-GC33 antibody or vehicle.…”
Section: Glypican 3 Targeted Therapy; Antibody-based Approachmentioning
confidence: 99%
“…161 Therefore, several anti-GPC3 mAbs have been produced for immunotherapy of HCC, but none of them can inhibit cell proliferation or induce apoptosis. [161][162][163][164] Feng et al 165 identified a human heavy chain variable domain antibody (HN3) targeting GPC3 by phage display technology and proved that HN3 could recognize a unique conformational epitope in the GPC3 core protein with high affinity. The HN3 inhibits cell growth in several hepatoma cell models in vitro and significantly inhibits the growth of HCC tumor-bearing node mice in vivo.…”
mentioning
confidence: 99%
“…The therapeutic monoclonal antibody against GPC3 has been developed which could induce antibody-dependent HCC cytotoxicity. Targeting GPC3 is able to inhibit tumor growth of HCC cell line xenograft (Ishiguro et al, 2008). Study also showed the concomitant treatment with GPC3 monoclonal antibody and sorafenib was more potent in preventing tumor growth than sorafenib alone in the HepG2 xenograft model (Ishiguro et al, 2008).…”
Section: Glypican-3mentioning
confidence: 96%
“…Targeting GPC3 is able to inhibit tumor growth of HCC cell line xenograft (Ishiguro et al, 2008). Study also showed the concomitant treatment with GPC3 monoclonal antibody and sorafenib was more potent in preventing tumor growth than sorafenib alone in the HepG2 xenograft model (Ishiguro et al, 2008). It is likely that targeting GPC3 could provide great clinical benefit during HCC management.…”
Section: Glypican-3mentioning
confidence: 97%